FACTORS INFLUENCING THE SUCCESS OF MASS MARKETING STRATEGIES IN TELECOMMUNICATIONS INDUSTRY: A CASE OF ORANGE KENYA LIMITED - Gioko, Charles Munene (European Journal of Business and Strategic Management, 2017)
Purpose: The purpose of the study was to assess factors influencing the success of mass marketing strategies in the telecommunication industry, a case of Orange Kenya Ltd. The study was to be guided by the following research objectives; to establish whether macro environment factors affect the success of a mass marketing strategy in telecommunication industry in Kenya, to determine whether competitive/industry environment factors affect the success of a mass marketing strategy in telecommunication industry in Kenya and to evaluate whether brand awareness efforts affects the success of a mass marketing strategy in telecommunication industry in Kenya. Methodology: The research design used for this study was random sampling. Primary data was collected using a structured questionnaire. The data collected was analyzed using descriptive statistics; frequencies, counts and percentages. The Statistical Package for Social Science (SPSS) was used as a tool to generate the frequencies that were used in excel tabulations. The data was presented using data tables and charts. Results: The study found out that macro environmental factors affect the marketing strategy. The study concluded that competitive/industry environment, Brand awareness, market research options, product development efforts and resources affect the success of mass marketing strategies. Unique contribution to theory, practice and policy: The study recommended to the telecommunication industry in Kenya to be on the lookout on emerging trends in the environments. They should frequently conduct environmental scanning and Competitive/industry analysis environment need to be frequently analyzed through SWOT analysis. The study also recommended that market research efforts need to be emphasized to enable them know the future and present expectations of their customers.